Dynamic imaging acoustic fields in research practice - Soldatov A. I. Aleksey Ivanovich; Макаров В. С. Виктор Степанович; Sorokin P. V. Pavel Vladimirovich; Kvasnikov K. G. Konstantin Grigorievich; Soldatov A. A. Andrey Alekseevich; Селезнев А. И. Антон Иванович; Kroening H. M. V. A. Hans Michael Wilhelm Adolf (2012, 2012)
Title screen